2016
DOI: 10.1103/physrevx.6.011008
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Sensorial Delay to Control Phototaxis and Emergent Collective Behaviors

Abstract: Collective motions emerging from the interaction of autonomous mobile individuals play a key role in many phenomena, from the growth of bacterial colonies to the coordination of robotic swarms. For these collective behaviors to take hold, the individuals must be able to emit, sense, and react to signals. When dealing with simple organisms and robots, these signals are necessarily very elementary; e.g., a cell might signal its presence by releasing chemicals and a robot by shining light. An additional challenge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
139
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(146 citation statements)
references
References 30 publications
(44 reference statements)
7
139
0
Order By: Relevance
“…Our results should be relevant and helpful for the interpretation of experiments of mixtures of passive and active colloids [3][4][5][6]18], polar and apolar vibrated disks [37] or even specially programmed robots [38,39]. Thereby, the interface propagation can be identified via w ( ) S q, in scattering experiments or by direct observation.…”
Section: Discussionmentioning
confidence: 80%
“…Our results should be relevant and helpful for the interpretation of experiments of mixtures of passive and active colloids [3][4][5][6]18], polar and apolar vibrated disks [37] or even specially programmed robots [38,39]. Thereby, the interface propagation can be identified via w ( ) S q, in scattering experiments or by direct observation.…”
Section: Discussionmentioning
confidence: 80%
“…Then, in 1995, Vicsek and coauthors introduced the Vicsek model [5], where a swarm is modelled by a collection of active particles moving with constant speed and tending to align with the average direction of motion of the particles in their local neighbourhood; this was first model that considered collective motion in terms of a noise-induced phase transition. Later, several additional models have been introduced to capture the properties of collective behaviours [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond its intrinsic scientific interest, a deep understanding of collective behaviours can contribute to applications in, e.g., swarm robotics, autonomous vehicles and high-accuracy cancer treatment [1,18,19]. In fact, the models employed to describe collective behaviours have also been fruitfully exploited in order to build artificial systems with robust behaviours arising from interactions between very simple constituent agents [9,10,14,20,21]. Furthermore, there is interest in understanding how these behaviours are influenced by the properties of the environment and, in particular, by the presence of obstacles, topological features and other particles [1,17,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike passive Brownian ratchets, active ratchets do not require the application of an external driving force to produce rectification [2][3][4]. Experimental studies [5][6][7][8][9][10][11][12][13][14][15] have shown the key role of self-propulsion for rectifying particle motion in different structures, such as an array of asymmetric funnels [5], a nanosized ratchet-shaped wheel [6], the asymmetric barriers [8], the microtubule bundles [9], the microscopic gears [11], and the nanoliter chambers [15]. Active ratchet effects and variations on them will open a wealth of possibilities such as sorting, cargo transport, or micromachine construction.…”
Section: Introductionmentioning
confidence: 99%